2022
DOI: 10.3390/coatings12070957
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of PMMA Functionalized with CuFe2O4/Cu2O/CuO Nanoparticles

Abstract: We have prepared a composite thin coating by incorporation of CuFe2O4/Cu2O/CuO nanoparticles in polymethyl methacrylate (PMMA) matrix by using the solution casting method. The electrical explosion of two twisted wires (EETW) was used to obtain multicomponent CuFe2O4/Cu2O/CuO nanoparticles with an average particle size of 20–70 nm. The microscopic studies showed that the nanoparticles in the composite coatings are evenly distributed. However, nanoparticles are strongly agglomerated as the powder concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The inclusion of multicomponent CuFe 2 O 4 / Cu 2 O/CuO NPs in the polymethyl methacrylate (PMMA) matrix was carried out for enhanced antibacterial properties. The NPs-PMMA dispersion in acetone solution cast on a slide resulted in an antibiofilm nanocomposite [58]. Jay et al synthesized CH-functionalized nanostructured NiFe 2 O 4 (n-NiFe 2 O 4 -CH) thin film onto the indium tin oxide (ITO) glass substrate via this simple method [59].…”
Section: Solution Casting Methodsmentioning
confidence: 99%
“…The inclusion of multicomponent CuFe 2 O 4 / Cu 2 O/CuO NPs in the polymethyl methacrylate (PMMA) matrix was carried out for enhanced antibacterial properties. The NPs-PMMA dispersion in acetone solution cast on a slide resulted in an antibiofilm nanocomposite [58]. Jay et al synthesized CH-functionalized nanostructured NiFe 2 O 4 (n-NiFe 2 O 4 -CH) thin film onto the indium tin oxide (ITO) glass substrate via this simple method [59].…”
Section: Solution Casting Methodsmentioning
confidence: 99%
“…Figure 11 shows the effect of the synthesized samples on the viability of S. aureus, P. aeruginosa and MRSA bacterial strains, as well as C. albicans fungi. The antibacterial activity of the PMMA/NP composites was previously investigated by us in the article [39]. It was found that a mass fraction of nanoparticles in the composite of less than 5% weakly inhibited bacterial growth.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Considering the abundant resources of Cu and its low cost in comparison to other particles such as Ag, CuO NPs can be used for their antibacterial, antifungal, and mechanical properties in prosthetic dentistry. Recent researchers revealed the antimicrobial effect of PMMA containing CuO NPs [ [22] , [23] , [24] ]. A recent study showed that adding CuFe2O4/Cu2O/CuO nanoparticles in the amount of 5 wt% can significantly enhance the antimicrobial effect of the resin [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent researchers revealed the antimicrobial effect of PMMA containing CuO NPs [ [22] , [23] , [24] ]. A recent study showed that adding CuFe2O4/Cu2O/CuO nanoparticles in the amount of 5 wt% can significantly enhance the antimicrobial effect of the resin [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation